Penggunaan kaedah analisis regresi teguh untuk menentukan kecekapan relatif - Mahat, Nor Idayu; Ismail, Wan Rosmanira (Jabatan Matematik Universiti Teknologi Malaysia, 2002)
This study discusses the use of robust regression analysis using the least trimmed of squares method to evaluate the relative efficiency of decision making units in organizations in the case of the existance of outliers and the effect of nonhomogeneus outside factor. Efficiency unit evaluated in this study is the efficiency of hospital physicians where the service cost is the input and the number of high severity discharges and low severity discharges of patients as the outputs. The results show that the estimation of the unit efficiency using LTS method is more stable.